Intergranular stress corrosion cracking of 13Cr weldable martensitic stainless steels - Maier, Jens (Curtin University, 2012)
Weldable martensitic stainless steels (13Cr) used in the oil and gas industry can suffer from intergranular stress corrosion cracking (IGSCC). In this study, sensitisation in the heat-affected zone of welds that can cause intergranular attack and IGSCC under service conditions was characterised. By using electrochemical measurements in combination with scanning probe microscopy, sensitised zones were detected along delta-ferrite precipitates that were formed during welding. A correlation between delta-ferrite and susceptibility towards IGSCC was established.